Urban Vulnerability Analysis Against earthquake hazard With the ELECTRE FUZZY method (Case Study: Karaj Metropolis) - Fatemeh Khodadadi; Mojgan Entezari; Farzaneh Sasanpour (تحقیقات کاربردی علوم جغرافیایی)
Today, in view of the growing population and population density in urban areas, especially in densely populated and susceptible cities, the need for an inclusive and comprehensive approach to natural disasters and disasters caused by their occurrence has become more evident . Focusing more than the size of the population in specific urban areas, lack of preventive planning and lack of readiness to deal with accidents such as earthquakes, is a very serious and important threat to citizens and the survival of the city. The capital city of Karaj, as one of the major cities in Iran, has a high risk of earthquakes due to the presence of several active faults inside and outside it. Accordingly, investigations of the seismic vulnerability of this city are one of the necessities of Karaj city management. Regarding this, the metropolis of karaj was selected as the study area. The method of research and analysis of information collected based on database-based methods using the ELECTRE FUZZY model and Criteria for building materials, number of floors, quality of buildings, population density, building density, area of parts, width of passageways, geology, distance from faults, distance from medical centers, distance from public space, distance from urban facilities and travel compatibility for research purposes Were used. The results indicate that 6, 8, 1, and 7 areas of Karaj municipality are vulnerable to earthquake, so that more than 70 percent of Karaj city is vulnerable to earthquake vulnerability on low and low floors and Only about 20% of the city of Karaj due to its proximity to the fault and the high density of population, construction and ... is in high and high risk areas. According to the principles of urban planning, the regulations of 2800 can cover earthquake damage in these areas.